Cyclosporine and Herbal Supplement Interactions. (12th January 2014) - Colombo, D.; Lunardon, L.; Bellia, G.
Abstract : Cyclosporine (CyA) is a well-known immunosuppressant with a narrow therapeutic window. Its bioavailability is affected by many other traditional drugs and herbal extracts. Cytochrome P-450 isoenzymes CYP3A4 and CYP3A5 and protein P-glycoprotein (P-gp) are involved in CyA bioavailability. Interactions of CyA with herbal extracts are not well known, but, given their increased concomitant use, it is important to know which extracts, many of which are commonly self-prescribed, can affect CyA blood concentrations. Decreased CyA blood concentration has been shown with St John's wort in case reports and, in vivo animal studies, with ginger, liquorice, scutellariae radix, and quercetin. Increased CyA concentration has been reported in patients with grapefruit juice, chamomile, or berberine, and with cannabidiol or resveratrol in animal studies. Effects of Echinacea and Serenoa repens on CyA levels have not been shown consistently, but concomitant use should be avoided. Although findings from animal studies cannot be directly translated into humans, avoiding concomitant use of herbal extracts is prudent until human clinical studies have ruled out any possible interaction. Clinicians should interview their patients carefully about their use of herbal supplements before CyA administration, and those receiving CyA should be warned about possible interactions between herbal preparations and CyA.